“I See Students Differently”: Following the Lead of Maker Educators in Defining What Counts as Learning - Bevan, Bronwyn; Ryoo, Jean J.; Vanderwerff, Aaron; Wilkinson, Karen; Petrich, Mike (Frontiers in Education, 2020)
With the expansion of maker programs in school and out-of-school settings, investigating the connections between making and learning are important for many reasons, not least to build the evidence base needed by educators committed to its practice. In this paper, we argue that, as a relatively new area of inquiry, studies of making can benefit from close dialogue between researchers and the practitioners who have both pioneered and continue to develop the practice. We share how a research-practice partnership sought to amplify the voices of informal educators leading afterschool maker programs to address the research question: How can afterschool making programs support student learning that is valued and relevant to the school day? We show how the research-practice partnership helped to refine a tinkering design framework in ways that reflect the values and expert knowledge of informal educators committed to liberatory forms of education for young people, particularly those from socio-economically and racially marginalized communities.